One parent’s advice to another : an exploration of self-care for parents of children with high-need disabilities and the development of a psychoeducational resource : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Manawatū, New Zealand - Oskam, Jana Aria Dunlop (Massey University, 2020)
Currently over 95,000 children are affected by a disability in New Zealand (NZ), making up 11% of the child population (Statistics New Zealand, 2013). Receiving a childhood disability diagnosis can be a life-changing event for the entire family. As current societal structures require parents to assume unforeseen caregiving roles (that typically last the course of their child’s lifetime), parents as informal caregivers make up a significant sector within NZ. Nevertheless, the dominant approach to research in the field of childhood disability has been based on the assumption that informal caregiving results in adverse outcomes for parents. Consequently, existing research has largely focused on the well-documented negative impact of caregiving for parents and their families. Although evidence suggests that effective self-care may act as a mediator against caregiver stress, few studies have approached informal caregiving from a positive psychology and health-promotion perspective. However, it can be argued that by adopting a positive health promotion perspective, we can improve understanding on how best to promote wellbeing for parents, and consequently, their children and families as well. Through two studies, this thesis explored the experience of self-care and wellbeing for parents of children with high-need disabilities (HND). Study One achieved this by interviewing 11 parents of children with high-need cerebral palsy or autism. Thematic analysis found that participants typically experienced and enacted self-care in four key areas, including parents’ 𝘍𝘰𝘳𝘮𝘢𝘭 𝘚𝘶𝘱𝘱𝘰𝘳𝘵𝘴 𝘢𝘯𝘥 𝘙𝘦𝘴𝘰𝘶𝘳𝘤𝘦𝘴, 𝘐𝘯𝘧𝘰𝘳𝘮𝘢𝘭 𝘙𝘦𝘭𝘢𝘵𝘪𝘰𝘯𝘴𝘩𝘪𝘱𝘴, 𝘝𝘢𝘭𝘶𝘦𝘴 𝘢𝘯𝘥 𝘎𝘰𝘢𝘭𝘴, and their use of 𝘛𝘪𝘮𝘦. In line with a transformative framework, Study Two developed a psychoeducational resource, aimed at enhancing parents’ self-care and perceived wellbeing, by integrating findings from the first study with existing literature. Preliminary evaluation of the resource booklet was achieved by 14 participants completing a written questionnaire to obtain parents’ feedback. Descriptive statistics and thematic analysis of participants’ responses identified that the booklet appears to capture parents’ experiences of self-care when raising a child with HND. Two key themes included participants’ 𝘗𝘰𝘴𝘪𝘵𝘪𝘷𝘦 𝘙𝘦𝘮𝘢𝘳𝘬𝘴 and 𝘐𝘥𝘦𝘢𝘴 𝘧𝘰𝘳 𝘊𝘩𝘢𝘯𝘨𝘦. Overall, findings suggest that despite caregiving challenges, there are effective self-care strategies which parents use to mitigate these risks and improve wellbeing.
Keywords: Parents of children with disabilities; Health and hygiene; Mental health; New Zealand; Attitudes; Self-care, Health; 170106 Health, Clinical and Counselling Psychology